THE EFFECT OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON THE USAGE INTENTION OF SELF-APPOINTMENT ON MYSILOAM APPS MEDIATED BY TRUST - Laurentia Cindy Gani Wijaya; Hery Winoto TJ (CV. Radja Publika, 2025)
Introduction: Appointment system is very important for people who often have busy schedules to ensure that no time is wasted. Patients mostly dissatisfy on consultation waiting time when they go to the outpatient department. By making it easier for them to make their own appointments, hospitals can also improve operational efficiency. Web-based Appointment System (WAS) in real time model that have been integrated into mobile phone applications such as MySiloam apps can be a strategy though the adoption is still not optimal. Aim: To assess if the perceived usefulness (PU) and perceived ease of use (PEOU) application can influence on the usage intention of the self-appointment feature in the MySiloam application and trust can be a mediator. Method: A quantitative method. The quiestionnaire data from 106 samples was analyzed using Structural Equation Model (SEM) approach. SEM analysis and hypothesis testing using the WarpPLS application with the Partial Least Squares (PLS) method. Results: MySiloam users at RS K Jakarta mostly are women aged 17-30 years with a bachelor's degree and work as employee. Analysis results show that PU and PEOU has a significant positive effect on trust of MySiloam user. Perceived Usefulness does not have a significant effect on intention to use while PEOU has. Trust also has a significant positive effect on the intention to use MySiloam. Indirectly, PU has a significant positive effect on the intention to use MySiloam mediated by trust while PEOU does not have significant effect through trust. Discussion: The hypothesis in this study was rejected because the results were not significant, meaning that the perception of usefulness in the MySiloam application did not have a major impact on the intention to use of MySiloam users. It can happen because the factors that influence usage intention of an application are various such as user experience, application quality and hospital responsiveness. Therefore, users may find MySiloam useful but do not intend to use it because there are other factors that are more influential in their considerations. This also happened in other study where the users felt it doesn’t make any difference to use application or go directly to the hospitals. Thus, application developers should consider all of the factors and promote the benefit of MySiloam especially in PEOU and trust so that users will have more intention to use it.